The Glycemic Effects of Pomegranate Juice - Wang, Jing (Curr Dev Nutr, 2020)
OBJECTIVES: We recently showed that a single dose of pomegranate juice (PomJ) intake reduced fasting glucose and increased insulin in young healthy subjects. Our study aims to determine the responses of blood glucose as well as principle hormones involved in glucose homeostasis (insulin, C-peptide, glucagon and gastric inhibitory polypeptide (GIP)) after consuming a single dose of 8 oz PomJ, glucose/fructose dissolved in water compared to water in healthy subjects. METHODS: 21 Healthy, normal weight individuals (BMI of >18 to 26.9 kg/m(2), fasting serum glucose < 100 mg/dL) were recruited. Volunteers were randomly assigned to take a single dose of 8 oz of water, PomJ, or water with 18.6 g of glucose + 18.3 g of fructose to match PomJ sugar content, followed by 1-week wash out, and crossover to other interventions in a random order. Fasting blood was collected before, and at 15, 30, 60, 90, 120, 150 and 180 minutes (min) after the drink. Serum glucose was measured enzymatically (Cayman) and insulin, C-peptide, glucagon, and GIP were analyzed using the multiplex human cytokine panel (Millipore). RESULTS: 21 healthy volunteers were divided in to 2 groups according to the fasting serum insulin levels: healthy subjects with low fasting serum insulin ≤995 pg/mL (LFSI, n = 12) and healthy subjects with high fasting serum insulin >995 pg/mL (HFSI, n = 9). In all subjects, water intake did not change the levels of glucose and hormonal markers. In LFSI subjects, significant lower glucose at 15 min and GIP at both 15 min and 30 min were observed after PomJ compared to sugar water intake. The area under the curve of serum GIP from LFSI volunteers consuming PomJ was lower compared to sugar water. The levels of insulin, C-peptides and glucagon in response to PomJ and sugar water intake were similar. In HFSI subjects, levels of glucose, C-peptide and glucagon in response to PomJ and sugar water intake were similar. Significant higher insulin at 15 and 30 min, and lower GIP at both 15, 30 and 60 min were observed after PomJ compared to sugar water intake. CONCLUSIONS: Compared to identical amount of sugar in water, lower glucose response was observed after Pom J in LFSI subjects while higher insulin level and decreased GIP level in HFSI subjects without any difference in glucose. Our data suggest that components in PomJ likely regulate individuals’ glucose metabolism. FUNDING SOURCES: Center for Human Nutrition.